Design Analysis and Analysis of Roof Structure Work in the Implementation of the Exit Gate and Cafeteria Construction Project at Delta Surya Sidoarjo Hospital - Djoni Irianto; Muhammad Maulana Gustian (Engineering And Technology Journal, 2024)
Building design and planning requires a very high level of precision and a relatively long time. Therefore, most consultants and construction implementers (contractors) rely on technical application support during project planning, design, and construction report preparation. A very commonly used application in Indonesia is AutoCAD. Supported with other applications such as SAP2000 and ETABS to create 2D and 3D images and analyze the strength of structures. The definition of design methods is the ways in which a designer creates an object. Some of the design methods that are often used are as follows: a. Explosing, which is a design method by seeking inspiration through critical thinking to produce a design that has never been created. b. Redefining, which is a design method by reprocessing a design to become something different and better. c. Managing, which is a design method by creating designs in a sustainable and continuous manner. d. Phototyping, which is a design method by improving and/or modifying the design of the ancestral heritage. e. Trendspotting, which is a design method by creating a design based on a developing trend. In the implementation process, the contractor PT Muliif Teknika Utama requires technical drawings that are used for work references. Where later the field results will be in accordance with the planning time. In the process of work on the structure of the field team, the implementation team needs shop drawings as a reference for implementation. Here is an example of a working drawing of a roof plan. Based on the results of the observations that have been made, the design needed in the work of the roof of the exit gate and cafeteria in the hospital. Delta Surya Sidoarjo includes: a. Drawing of the roof truss plan b. Drawing of the roof component plan in the form of placing curtains, rafters, battens, and breising column c. Cut drawings d. Detail drawings.